Monetary-Fiscal-Trade Policy and Economic Growth in Pakistan: Time Series Empirical Investigation - Jawaid, Syed Tehseen; Qadri, Faisal Sultan; Ali, Nasir (International Journal of Economics and Financial Issues, 2011)
This study empirically examines the effect of monetary, fiscal and trade policy on economic growth in Pakistan using annual time series data from 1981 to 2009. Money supply, government expenditure and trade openness are used as proxies of monetary, fiscal and trade policy respectively. Cointegration and error correction model indicate the existence of positive significant long run and short run relationship of monetary and fiscal policy with economic growth. Result also indicates that monetary policy is more effective than fiscal policy in Pakistan. In contrast, trade policy has insignificant effect on economic growth both in the short run and in the long run. In light of the findings, it is suggested that the policy makers should focus more on monetary policy in order to ensure economic growth in the country. It is also recommended that further research should be conducted to find out such components of exports and imports which lead to the ineffectiveness of trade policy to enhance economic growth in Pakistan. Keywords: Monetary; Fiscal; Trade; Economic Growth JEL Classifications: E42; E62; F13; F43